CARBONIFEROUS FORAMINIFERAL PALEOBIOGEOGRAPHY IN TURKEY AND ITS IMPLICATIONS FOR PLATE TECTONIC RECONSTRUCTIONS (Rivista italiana di Paleontologia e Stratigrafia, 2003)
Four foraminiferal paleobiogeographic realms are distinguished in the Carboniferous – North Paleotethyan, Perigondwanian, Siberian and North American. The Carboniferous foraminiferal faunas of both the Istanbul and Anatolide-Tauride zones distinctly differ from both Cimmerian terranes (Central Afghanistan, Qiangtang) and Libya and Egypt of the Perigondwana Realm and show close relation to the North Paleotethyan Realm, especially to the Fennosarmatian Province of southeastern Laurussia (Moesian and Scythian platforms) or to the Central Asiatic Province. A model that best fits with available evidence is that the Anatolide-Tauride Zone was either a part or located close to Laurasia in Carboniferous. The Istanbul Zone represents an equivalent of the Rhenohercynian Zone of the Central Europe and can not be compared with Intra-Alpine or south Variscan terranes which may be correlated with the Anatolide-Tauride Zone. Later, in the Permian, the Anatolide -Tauride Zone may has been separated from the Eurasian mainland by the Karakaya back-arc ocean.